1999
DOI: 10.1093/ajcn/70.4.466
|View full text |Cite
|
Sign up to set email alerts
|

Effects of psyllium on glucose and serum lipid responses in men with type 2 diabetes and hypercholesterolemia

Abstract: Background: Water-soluble dietary fibers decrease postprandial glucose concentrations and decrease serum cholesterol concentrations. This study examined the effects of administering psyllium to men with type 2 diabetes. Objective: The objective was to evaluate the safety and effectiveness of psyllium husk fiber used adjunctively to a traditional diet for diabetes in the treatment of men with type 2 diabetes and mild-to-moderate hypercholesterolemia. Design: After a 2-wk dietary stabilization phase, 34 men with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
141
1
17

Year Published

2002
2002
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 209 publications
(169 citation statements)
references
References 40 publications
(27 reference statements)
5
141
1
17
Order By: Relevance
“…The reduction observed for LDL cholesterol by Davidson et al (1998) in hypercholesterolaemic patients after being treated with 10.2 g psyllium per day during 24 weeks was also slightly lower (5.3%) than our value. On the other hand, our results were slightly lower than those found by Anderson et al (1999) in men with type 2 diabetes and hypercholesterolaemia after 8 weeks receiving 10.2 g psyllium daily. Romero et al (1998) observed that LDL cholesterol concentrations were reduced by an average of 22.6 and 26% after administering 1.3 g=day of psyllium to healthy volunteers.…”
Section: Discussioncontrasting
confidence: 97%
See 1 more Smart Citation
“…The reduction observed for LDL cholesterol by Davidson et al (1998) in hypercholesterolaemic patients after being treated with 10.2 g psyllium per day during 24 weeks was also slightly lower (5.3%) than our value. On the other hand, our results were slightly lower than those found by Anderson et al (1999) in men with type 2 diabetes and hypercholesterolaemia after 8 weeks receiving 10.2 g psyllium daily. Romero et al (1998) observed that LDL cholesterol concentrations were reduced by an average of 22.6 and 26% after administering 1.3 g=day of psyllium to healthy volunteers.…”
Section: Discussioncontrasting
confidence: 97%
“…Earlier studies reported that psyllium reduced fasting serum glucose concentrations in individuals with type 2 diabetes (Fagerberg, 1982) and in type 2 diabetic patients with chronic portalsystemic encephalopathy (Uribe et al, 1985). Other studies demonstrated that different preparations of ispaghula husk lowered postprandial serum glucose concentrations in type 1 (Florholmen et al, 1982), in type 2 diabetic patients (Sartor et al, 1981;Pastors et al, 1991;Anderson et al, 1999), in healthy volunteers (Sierra et al, 2001) and in both healthy and type 2 diabetic subjects (Jarjis et al, 1984). Fibre doses used were different, ranging from 3.6 g administered with breakfast (Florholmen et al, 1982) to 35 g per day administered as a dietary supplement (Uribe et al, 1985).…”
Section: Discussionmentioning
confidence: 98%
“…The ability of AX-rich fibre to lower blood glucose appears related to its viscous, soluble nature. Other soluble fibres including guar gum (Torsdottir et al, 1991), b-glucan (Juntunen et al, 2002), konjac-mannan (Vuksan et al, 1999) and pysllium (Anderson et al, 1999) have similarly been found to confer metabolic benefit in people with Type II diabetes. The advantage of AX-rich fibre here lies in its high palatability (Lu et al, 2000a).…”
Section: Discussionmentioning
confidence: 99%
“…However, the levels of fibre required to induce these beneficial effects are high (up to 50 g/day) (Franz et al, 2002) and difficult for people accustomed to Western diets to achieve (Alaimo et al, 1994). For this reason, the effects of purified soluble fibre supplements including guar gum (Groop et al, 1993), beta-glucan (Wursch & PiSunyer, 1997), konjac-mannan (Vuksan et al, 1999) and psyllium (Anderson et al, 1999) have been explored. In this study, we examine the effects of arabinoxylan-rich (AX) fibre, because of its particular acceptability and palatability (Lu et al, 2000a) as a potentially even more useful fibre supplement for people with Type II diabetes.…”
Section: Introductionmentioning
confidence: 99%
“…Psyllium in a supplemental drink form, has been specifically shown to lower postprandial glycemia in individuals with Type 2 DM when consumed just before a meal (Anderson et al, 1999;Sierra et al, 2002) and to have a residual effect after a second meal (Pastors et al, 1991;Anderson et al, 1999). Few studies have examined second meal responses to soluble fiber (Pastors et al, 1991;Sierra et al, 2002), but there is limited data on glycemic load and soluble fiber in influencing Type 2 DM (Salmeron et al, 1997;Liu et al, 2000).…”
Section: Introductionmentioning
confidence: 99%